Identification of Single Nucleotide Polymorphism Marker and Association Analysis of Marbling Score in Gene of Hanwoo - Seung-Chang Kim; Seung-Hwan Lee; Ji-Woong Lee; Tae-Hun Kim; Bong-Hwan Choi (Asian-Australasian Journal of Animal Sciences, 2016)
The Fas (APO-1, TNFRSF6) gene known as a member of the tumor necrosis factor receptor superfamily was selected for DNA marker development in Korean cattle. It is a cell membrane protein and mediates programmed cell death (apoptosis). We discovered single nucleotide polymorphisms (SNPs) within Fas gene in order to develop novel DNA markers related to economical traits at the genomic level. The sequences of whole exon and 1 kb range of both front and back of the gene were determined by direct-sequencing methods using 24 cattle. A total of 55 SNPs were discovered and we selected 31 common polymorphic sites considering their allele frequencies, haplotype-tagging status and linkage disequilibrium (LD) for genotyping in larger-scale subjects. The SNPs were confirmed genotype through the SNaPshot method (n = 274) and were examined for a possible genetic association between Fas polymorphisms and marbling score. So, the SNPs that were identified significant are g.30256G>C, g.31474C>A, g.31940A>G, and g.32982G>A. These results suggest that SNPs of Fas gene were associated with intramuscular fat content of meat quality traits in Korean cattle.